If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 4 = 2y + -6 Reorder the terms: 4 + 4y = 2y + -6 Reorder the terms: 4 + 4y = -6 + 2y Solving 4 + 4y = -6 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4 + 4y + -2y = -6 + 2y + -2y Combine like terms: 4y + -2y = 2y 4 + 2y = -6 + 2y + -2y Combine like terms: 2y + -2y = 0 4 + 2y = -6 + 0 4 + 2y = -6 Add '-4' to each side of the equation. 4 + -4 + 2y = -6 + -4 Combine like terms: 4 + -4 = 0 0 + 2y = -6 + -4 2y = -6 + -4 Combine like terms: -6 + -4 = -10 2y = -10 Divide each side by '2'. y = -5 Simplifying y = -5
| -9a-3a=-43 | | 4(4x-5)=3(2x+1+2) | | 3x-2=5x+9 | | (3c-4)(4c-6)=x | | 6x+7=-2(x-6) | | 1/10(63-4a)=a/2 | | 46= | | 3(4x+5)=14X+14-2X+1 | | r+9.4=4.2 | | 10=12-3x | | 26x-10-18x=4(2x-3)+2 | | 6n+6n=-9(n+11)+9(11n+11) | | 5(x-1)-4=-3(2x-5)-2 | | -7r=3r-8 | | 8y-4=12y+20 | | x+(x-12.6)=65.4 | | 4(x+1)+17= | | 5(x-6)+4=7(x+2)-6 | | -26-21.2g=16.3g-66.18 | | x+9=2x+25 | | 5-3x-3=-1-6 | | 5x-15=4x+6 | | 8x-5=6x+33 | | 120+4m=150+10m | | 4+3x=10x-17 | | 8x-6=7x+1 | | 120-4m=150-10m | | 120-4m=150-10 | | 9x-2=6x-47 | | 2n=-9n-9 | | 4y-6+5y-8= | | 120+10m=150+4m |